Elaborating on the effect of culture on the relations of extraversion and neuroticism to life satisfaction. (1st May 2019) - Lun, Vivian Miu-Chi; Yeung, June Chun
Abstract: The Five Factor Model (FFM) of personality has been repeatedly found to predict life satisfaction (LS), but cultural variations have been noted in the effects of each FFM dimension. In this research, we compared the prediction of LS with Extraversion and Neuroticism via the pathways of individual depressive state and interdependent happiness between American ( n  = 155) and Chinese community adults ( n  = 248). In both samples, Extraversion and interdependent happiness positively predicted LS, whereas Neuroticism and depressive state negatively predicted LS. Using structural equation modeling, we found that interdependent happiness mediated the effects of Extraversion and Neuroticism on LS in both samples, and there was no significant cultural difference in the indirect effect of interdependent happiness. Depressive state mediated the effect of Neuroticism on LS in American adults, but it did not explain the effects of Extraversion and Neuroticism on LS for the Hong Kong Chinese adults. We interpret the different effect of depressive state by referring to the literature on cultural differences in emotion. These findings support the notion that the specific effect of each FFM dimension on LS should be examined with reference to the cultural context. Highlights: Extraversion and Neuroticism predict life satisfaction (LS) for both American and Chinese adults. Depressive state explains the effect of Neuroticism on LS for American but not for Chinese adults. Interdependent happiness explains the effect of Extraversion and Neuroticism on LS in both groups.